Knowing Where You Are Heading: Innovation and Innovation Policy in Iceland 2003-2022 - Ottósson, Hannes; Sæmundsson, Rögnvaldur Jóhann (Stofnun stjórnmála og stjórnsýslu, 2024)
As awareness of the importance of innovation has increased, governments around the world have become increasingly interested in strenghtening innovation and have set policies for that purpose. The goal of this study is to increase understanding of how government policy affects the development of innovation and thereby support governments in learning from past experiences and tailoring its policy to local conditions. The theoretical foundations of this study are based on previous studies of innovation and innovation policy. In the study, the innovation policy and the development of innovation in Iceland are analyzed over a 20-year period, from 2003 to 2022. Text analysis and descriptive statistics are used to assess the content of the policy, the development of innovation and the coherence between policy and development. The results are that the major aim of the policy was to create a knowledge-based society and to support research and development in order to create an additional pillar for carrying the Icelandic economy. Revenues and the number of new firms in innovative industries have grown considerably during the period, although the growth did not exceed the economy as a whole. The policy was found to be consistent with the development of innovation during the period even if it is questionable if a new pillar emerged. Further research on the interaction between innovation policy and the development of innovation in Iceland has the potential to increase general knowledge in this field and improve our understanding of the conditions that exist in Iceland and how individual policy instruments used by the Icelandic government affect the level and success of innovation. Samhliða aukinni meðvitund um mikilvægi nýsköpunar hafa stjórnvöld víða um heim í auknum mæli haft áhuga að efla nýsköpun og sett sér sérstaka stefnu af því tilefni. Tilgangur þessarar rannsóknar er að auka skilning á því hvernig stefna stjórnvalda hefur áhrif á þróun nýsköpunar og þar með að aðstoða stjórnvöld við að læra af fyrri reynslu og ...